Antioxidant properties of Morinda citrifolia L. and their effects on haemostasis parameters - Abdul Karim, Mohd Arif (2014)
This study aims to determine the antioxidant properties of Morinda citrifolia (M. citrifolia) fruit crude extracts and its effects on the blood haemostasis parameters. Extracts used in this study were M. citrifolia fruit crude aqueous and ethanolic extracts (MFCAE and MFCEE). 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and β-carotene bleaching assay were conducted to determine antioxidant activity. Ascorbic acid (ASA) and butylated hydroxytoluene (BHT) were used as standard antioxidants. Total phenolic content was determined spectrometrically according to the Folin-Ciocalteu’s method and expressed as Gallic acid equivalent (GAE). The effects on blood haemostasis parameters were determined by using in vitro and in vivo models. In vitro model was done by determination the effect on haemostasis tests which include prothrombin time (PT), activated partial thrombosplastin time (APTT), and platelet aggregation tests where the human blood samples were treated with different concentrations (10, 20, 30, 40, 50mg/mL) of MFCAE and MFCEE. Blood collected from 58 respondents were prepared to obtain platelet rich plasma (PRP) and platelet poor plasma (PPP) for coagulation (PT, APTT), and platelet aggregation test respectively. In in vivo model, 48 Sprague Dawley rats were treated with different dosage (7.5, 75, 750mg/kg) of MFCAE. Their blood samples were subjected for haemostasis parameter tests which include full blood count, PT, APTT, platelet aggregation, and bleeding time. The highest percentage of inhibition by MFCAE against DPPH radicals was 27.21 ± 1.24%, 61.78 % lower when compared to ASA. β-carotene bleaching assay showed the percentage of antioxidant activity of MFCAE was 78.96%, 13.6% lower than BHT. Total phenolic content of MFCAE was 281.83 ± 14.78mg GAE/100g. In vitro model showed that MFCAE and MFCEE were significantly prolonged the PT and APTT in dose dependant manner. The highest measureable value was at the concentration of 40mg/mL. The highest PT and APTT were 55.97 ± 14.54 and 114.74 ± 11.53 seconds for MFCAE; and 58.27 ± 15.69 and 118.03 ± 10.18 seconds respectively for MFCEE. However this anticoagulant property for the in vivo model was not significantly observed as in vitro model. MFCAE exhibits some antiplatelet activity in both in vitro and in vivo model. This study showed MFCAE contains some antiplatelet activity with dose dependant manner when collagen was used as an agonist. Briefly, the findings suggest that M. citrifolia extracts may become a potential plant based anticoagulant and antiplatelet which should be effective and safe for patients with cardiovascular disorders. The presence of total phenolic in the extract may be partly responsible for the observed effects.